Proteomic analysis of rice storage protein in relation to nutrient quality of three different rice cultivars - Ramli, Nur Syazila; Mohamed Rehan, Aisyah; Md Zin, Noor Hasniza (Kulliyyah of Science, International Islamic University Malaysia, 2015)
Seed storage proteins (SSPs) are the most important component in rice which provides the nutrient to consumers. The SSPs content and composition are among the important determinant for rice quality determination specifically for nutritional value. Multiple factors have been identified to give effect to the nutritional value to rice grain including different types of cultivars. The purpose of this study is to investigate the expression level of SSPs of rice from three different cultivars. Besides that, this study also relates the nutrient quality of rice with the variability in SSPs expression of the three cultivars. The SSPs were extracted from three different rice cultivars which are white rice, brown rice and glutinous rice that are available in the market. Bradford Assay was carried out to determine the total SSPs content and brown rice was find out to have significantly higher total SSPs content compared to white rice and glutinous rice. On the other hand, the glutinous rice showed the lowest SSPs content out of the three tested rice cultivars. Based on the banding patterns of the SDS-PAGE, there were different level of expression was observed between the three rice cultivars. Among the three rice cultivars, protein pattern of white rice was quite similar with brown rice. In both rice cultivars, white and brown rice, there was high intensity of protein bands that appeared at 50kDa that compared to glutinous rice. Apart from that, the glutelin acid subunit between 40kDa and 50kDa of brown rice appeared to be more intense followed by white rice and glutinous rice. Regarding to the protein banding of glutelin basic subunit and prolamin, all the three cultivars exhibited the presence of protein band but with slightly difference in intensity. Thus, provide information on the proteomic analysis of different rice cultivars that can be closely related to the nutrient quality of these different rice cultivars.